Long-term renal prognosis among patients with primary Sjögren's syndrome and renal involvement: A nationwide matched cohort study. Issue 113 (September 2020) - Lin, Chun-Yu; Wu, Chun-Hsin; Chen, Hung-An; Hsu, Chung-Yuan; Wang, Li-Hui; Su, Yu-Jih
Abstract: Background: The long-term renal outcome in patients with primary Sjögren's syndrome (pSS) remains uncertain. We aimed to determine the absolute incidence and relative risk of chronic kidney disease (CKD) and end-stage renal disease (ESRD) in patients with pSS at the general population level. Methods: We performed a retrospective cohort study using a national health insurance database in Taiwan from 2000 to 2013. We calculated the cumulative incidence of CKD and ESRD in our pSS and age-, sex- and entry time-matched control cohorts. Cox regression analyses were used to estimate adjusted hazard ratios (aHRs) after adjusting for comorbidities and medications. Results: Among 17 505 patients with incident pSS, 1008 (5.8%) developed CKD and 38 (0.22%) developed ESRD. Of the 87 525 non-pSS controls, 3173 (3.6%) developed CKD and 256 (0.29%) developed ESRD. The risk of CKD was higher in patients with pSS than in the non-pSS controls (adjusted hazard ratio [HR] 1.49, 95% confidence interval [95% CI] 1.38–1.59). Notably, the risk of ESRD was similar in both pSS and non-pSS cohorts (aHR 0.82, 95% CI 0.58–1.16). Conclusions: Renal prognosis among patients with pSS and renal involvement is good. Although the risk of ESRD did not increase in patients with pSS, a significantly increased risk of CKD was observed in these patients, indicating the need for increased vigilance in regular monitoring for renal complications in patients with pSS. Highlights: This nationally representative, population-based cohort study demonstrated that 5.8% of patients with pSS had chronic kidney disease. Compared to an age- and sex-matched general population cohort, patients with pSS did not have an increased risk of end-stage renal disease. Regular monitoring of renal function is essential in pSS patients; however, physicians can assure patients that their renal prognosis is good.